Musculotendinous Disorders in the Upper Extremity: Part 2. MRI of the Elbow, Forearm, Wrist, and Hand - Fritz, Russell C.; Boutin, Robert D. (Seminars in Musculoskeletal Radiology, 2017)
Muscle and tendon injuries about the elbow and more distal aspect of the upper arm are commonly evaluated and characterized with magnetic resonance imaging. This article reviews our experience with muscle and tendon injury as well as denervation of muscles. We focus on abnormalities of the biceps and the triceps tendons about the elbow as well as abnormalities of the flexor and extensor tendons about the elbow, forearm, wrist, and hand. We also discuss and illustrate our experience with lacerations, crush injuries, and muscle hernias in the forearm.
Keywords: muscle; tendon; injury; strain; elbow; forearm; wrist; MRI